Synthesis and Characterization of Metallo-Supramolecular Polymers Based on Benzodipyrrolidone - Chi, Zheng; Dong, Hao; Shi, Ganhui; Liu, Pan; Ma, Chenchen; Chen, Xuegang (Frontiers in Chemistry, 2021)
A simple route to the preparation of benzodipyrrolidone (BDP) based monomeric building blocks containing 2,2´:6´,2´´-terpyridines is reported from a common precursor 4´-(4-pinacolatoboronphenyl)-2,2´:6´,2´´-terpyridine via Suzuki coupling reaction. Self-assembly polymerization with ruthenium (II) ions under mild conditions yielded a series of novel metallo-supramolecular polymers with weak donor-acceptor (D-A) structures based on benzodipyrrolidone. The structure of the bridge connected BDP with terpyridine have a significant impact on the wavelength and intensity of the intramolecular charge transfer (ICT) absorption peak. The resulting metallo-polymers exhibited strong double absorption bands around 315 nm and 510 nm involved in π-π* transitions and ICT or metal to ligand charge transfer (MLCT) absorption bands. The forming of D-A structure and coordination with ruthenium (II) ions is favorable to narrow the energy gap and the energy gaps of the resulting metallo-supramolecular polymers are 2.01 eV and 1.62 eV, respectively.